Severe acute respiratory disease in health-care workers during the influenza H1N1 pandemic in Argentina - Daniel Pryluka; Gustavo Lopardo; Lucia Daciuk; Daniel Stecher; Pablo Bonvehi (Journal of Infection in Developing Countries)
Introduction: During the 2009 influenza H1N1virus pandemic, health-care workers were exposed to elevated risk of infection. The aim of this study was to estimate the risk for severe acute respiratory disease (SARD) in this population during the pandemic period in Argentina.